Social Entrepreneurship: A Bibliometric Analysis Using R - Yapp, Yi Hui; Suddin Lada; Mat Salleh Ayub; Nor Fzlinda Fabeil (Penerbit UMS, 2023)
This research seeks to evaluate social entrepreneurship through bibliometric analysis. The study undertakes the effort to fully document the composition, number, trends, authorship, and source influence of knowledge as well as its growth. This research focuses on a searchable Scopus database of 245 articles that have been compiled and analyzed via R Studio from a vast number of studies over the last 17 years and are the most relevant. Preliminary findings show that between 2005 and 2022, there was a growth in the number of articles published related to social entrepreneurship. By performing a bibliometric study with R, it is possible to identify the subject's most relevant journals, authors, and publications. The study found that by condensing the most crucial elements of social entrepreneurship into a single concept, an innovative research topic can be formed, resulting in fresh research opportunities in the broad field of social entrepreneurship.